2021
DOI: 10.3389/fendo.2021.765916
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Sex Hormones and Hormonal Status With Arterial Stiffness in a Female Sample From Reproductive Years to Menopause

Abstract: ObjectiveLoss of sex hormones has been suggested to underlie menopause-associated increment in cardiovascular risk. We investigated associations of sex hormones with arterial stiffness in 19–58-years-old women. We also studied associations of specific hormonal stages, including natural menstrual cycle, cycle with combined oral contraceptives (COC) and menopausal status with or without hormone therapy (HT), with arterial stiffness.MethodsThis study includes repeated measurements of 65 healthy women representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…To investigate the RNA content of EV and HDL particles, we collected plasma samples after overnight fasting from a subset of “Estrogen, microRNAs and the risk of metabolic dysfunction (EsmiRs) study” (Laakkonen et al, 2021) participants, consisting of 18 postmenopausal women (age range 52–57 years, Table S1). Of these women, nine used estrogen-based hormonal therapy (HT), and nine were HT nonusers.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the RNA content of EV and HDL particles, we collected plasma samples after overnight fasting from a subset of “Estrogen, microRNAs and the risk of metabolic dysfunction (EsmiRs) study” (Laakkonen et al, 2021) participants, consisting of 18 postmenopausal women (age range 52–57 years, Table S1). Of these women, nine used estrogen-based hormonal therapy (HT), and nine were HT nonusers.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, arterial compliance increased significantly in hormone users after 4 weeks of cessation, but the authors did not report the route of estrogen administration or concomitant progestin use (18). Conversely, a recent crosssectional study (19) of 36 menopausal women reported that hormone therapy (six oral, two transdermal estrogen)-users had higher aPWV, consistent with greater cardiovascular risk, than postmenopausal non-users (n = 26), although the authors did not report whether hormone therapy included a progestin. Similar to studies examining the effect of postmenopausal hormone therapy on blood pressure, it is possible that factors other than the route of estrogen administration contributed to the reported outcomes, including differing methodologies to measure arterial stiffness (54).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have examined the impact of different routes of estrogen administration on vascular measures and have shown conflicting results (6,8,(14)(15)(16)(17)(18)(19), which is most likely due to differences in study populations, age and cause of menopause, timing of postmenopausal hormone initiation, and notably, the presence of progestin. The Women's Health Initiative (WHI), a trial in which postmenopausal women with a uterus were randomized to both oral conjugated equine estrogen (CEE) and medroxyprogesterone acetate (MPA) or placebo was stopped early due to negative cardiovascular outcomes in the intervention arm (3).…”
Section: Introductionmentioning
confidence: 99%
“…Sex hormones and their association with arterial stiffness is rather complex, especially in the women population with variable menstrual status. Laakkonen et al reported that age- and hormone-mediated associations in arterial stiffness cannot be differentiated, but still suggested that the potential role of sex hormones as hormonal status was differentially associated with arterial stiffness in age-group focused analyses ( 38 ). Overall, there may be a hormonal influence, albeit its power as a cardiovascular risk factor over other traditional risk factors may not be very strong.…”
Section: Discussionmentioning
confidence: 99%